2018
DOI: 10.1080/20009666.2018.1428023
|View full text |Cite
|
Sign up to set email alerts
|

Canakinumab and cardiovascular outcomes: results of the CANTOS trial

Abstract: IL-1 cytokines are mainly responsible for controlling a series of pro-inflammatory reactions induced in response to pathogen mediated tissue injury. Among the IL-1 cytokine family, IL-1 β results in upregulation of genes responsible for boosting immune system reactivity and inflammatory response. With growing pathophysiological relevance of IL-1β in a myriad of disease pathogenesis, new biological drugs have been developed in recent years. One such drug, Canakinumab, targeting IL-1β has been recently approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…A recent study has found that cytokine-based/anti-inflammatory therapy may be more efficacious in preventing cardiovascular disease than cholesterol-lowering compounds 42 . Results from the CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) trial show that the IL-1β inhibitor canakunumab, independent of lipid-lowering, significantly reduces the risk of cardiovascular disease and recurrent cardiovascular events in patients with previously diagnosed myocardial infarction 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that cytokine-based/anti-inflammatory therapy may be more efficacious in preventing cardiovascular disease than cholesterol-lowering compounds 42 . Results from the CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) trial show that the IL-1β inhibitor canakunumab, independent of lipid-lowering, significantly reduces the risk of cardiovascular disease and recurrent cardiovascular events in patients with previously diagnosed myocardial infarction 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, targeting inflammation using the biological therapy has previously been successful. Canakinumab, which neutralizes IL1B, reduced recurrent cardiovascular outcomes in patients with a high inflammatory burden in a clinical trial even though the results of this trial were substantially lower than expected [29]. The underlying mechanism for TNF-driven atherothrombosis could be via a variety of proposed mechanisms, including favourable effects on circul1ating lipids, insulin resistance, endothelial dysfunction, leucocyte recruitment, oxidative stress, vasodilation or coagulation [30].…”
Section: Primary Findings In Cardiovascular Diseasementioning
confidence: 99%
“…This large phase 3 clinical trial aimed at studying the cardiovascular outcomes of canakinumab‐mediated IL‐1β blockade. The trial showed that IL‐1β neutralization reduced the incidence of cardiovascular disease 224 . However, it did not reduce the incidence of new‐onset diabetes mellitus, 225 highlighting that pathophysiological conclusions drawn from preclinical research are in some instances too simplistic, and may neglect the more nuanced aspects of innate immune sensor regulation and simultaneous contributions of various immune components.…”
Section: Prospects For Future Therapeutic Applicationsmentioning
confidence: 99%